Virulent Zones : Animal Disease and Global Health at China's Pandemic Epicenter - Fearnley, Lyle; Project Muse. (Durham : Duke University Press, 2020)
"VIRULENT ZONES is an ethnography of the search for the origins of influenza pandemics in rural China. In the early 1980s, Hong-Kong based virologists pinpointed southern China as an origin for influenza pandemics due to the region's entanglements of farming practices, animal husbandry, and wet-rice paddy landscapes. One example is Poyang Lake, which is not only China's largest freshwater lake, but a wintering site for hundreds of thousands of migratory birds and the home of large-scale duck farming. According to popular imaginings of pandemic epicenters, scientists go to a remote place and find a discrete origin for a virus, which can then be transported back into a laboratory for further research. But for anthropologist Lyle Fearnley, Poyang Lake exemplifies the importance of what scientists call the non-virological, or other factors outside of the virus that are crucial to understanding the virus' spread, such as migration of wildlife species, rapid population growth, and an increase in livestock production. When taken into consideration, non-virological factors also affect the trajectory of research itself; rather than the epicenter functioning as a place from which a virus is extracted and taken to a laboratory, the epicenter, in this case Poyang Lake, becomes the site from which research is conducted. For Fearnley, this shift is crucial, as Poyang Lake serves as an example of a new form of scientific displacement, which is usually understood as the process through which research done in a laboratory is "displaced" into the real word-and vice versa-through carefully controlled experiments. But at Poyang Lake, where scientists and farmers share one habitat, Fearnley argues that elements of research are continually reproduced and changed, displacing scientific inquiry into new directions. And whereas in the traditional laboratory setting, scientific displacement from the field to the lab renders a power dynamic in which the researcher is more knowledgeable than the layperson, the research site of Poyang Lake-and its continuous displacement through encounters with farmers and farming practices-serves to disrupt the hierarchical relationship between layperson and scientist. What emerges at Poyang Lake, then, is not only a revaluation of the power dynamic at the heart of scientific study, but a new account of scientific research and agency"--
The origins of pandemics -- Pathogenic reservoirs -- Livestock revolutions -- Wild goose chase -- Affinity and access -- Office vets and duck doctors.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Zoonoses; Animals as carriers of disease; Agriculture -- Environmental aspects -- China -- Poyang Lake; Viruses -- Research -- China -- Poyang Lake; Influenza -- Research -- China -- Poyang Lake; Electronic books